"Enraizados Da Letra": Lyrics and the Letter in Brazilian, Cuban, and Haitian Rap. Issue 4 (31st March 2022) - Hankin, Charlie D.
Abstract : Several scholars have outlined the Afro-diasporic connections and semiotic features common to global iterations of hip-hop. This article proposes that what connects rappers in Brazil, Cuba, and Haiti is a specific redefinition of rap as intermedial writing. Guided by ethnographic insights, I trace the recurrent figure of writing through a corpus of songs released by Brazilian, Cuban, and Haitian rappers between roughly 2000 and 2015. Bringing together multiple sites of inscription and pathways into repente improvisation, pixação writing, samba lyricism, jazz-writing, written poetry, and activism, these rappers provide new theoretical tools for understanding intermediality as well as contemporary Afro-diasporic literature, rereading hip-hop from the Global South through the particularities of their own languages and histories. I argue that their reception of hip-hop is not only the product of shared oral/aural traditions but also a response to the specific politics of literacy that have shaped Latin America.